Le cru de l’écrit ou les archives de la sauvagerie - Alice Delmotte-Halter (Flaubert: Revue Critique et Génétique)
Hélène Cixous has a passion for manuscripts. In two interviews she told us of the importance of writing by hand, on a table. In this article I will try to understand the principles of her practice as a writer and her thoughts about writing by studying Osnabrück. Is writing cooking? Cooking and sewing practices, the former closer to Cixous’ writing (that sizzles) than the latter, appear as writing’s conceptual metaphors, themes that are clearly visible in the manuscripts but which later re-writing tends to erase. Writing at its birth is a wild writing, cruel and raw. The ethnocritic ethnographer here observes that the principles of taboo, prohibition and shame, are those that maybe reorganize the most strongly rewritings up to their final book form. Or how to make presentable life in its beauty and chaos.